Suppression of impulsive disturbances from audio signals - Lane, John E.; Kasparis, Takis (My University, 1993)
A simple and effective method is proposed for suppressing impulsive noise from audio signals with minimal high frequency loss. Suppression is accomplished by median filtering the contaminated signal sections. A gating signal that enables local median filtering is generated by an algorithm that involves impulse detection and recursive median filtering.
Keywords: Computational complexity; Algorithms; Image analysis; Image processing; Signal detection